2012
DOI: 10.1093/heapro/das035
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting hospitals in Lithuania: health professional support for standards

Abstract: SUMMARYThe standards for health promotion (HP) addressing five domains such as (1) management policy, (2) patient assessment, (3) patient information and intervention, (4) promoting a healthy workplace and (5) improving continuity and cooperation have been elaborated and applied within the International Networks of Health Promoting Hospitals (HPH). The awareness of HP activities by health professionals and their opinions as to the applicability of the five HP standards in three randomly selected hospitals of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…It has been suggested that professional groups respond differently to health promotion programs and that nurses are more supportive by comparison to doctors (Johansson, Stenlund, Lundström, & Weinehall, 2010;Misevicience & Zalnieraitiene, 2013). Correspondingly, Powell and Davies (2012), as outlined above, have found that nurses were more likely to implement pain-manage-ment services.…”
Section: Insider Coalitions With Nursesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that professional groups respond differently to health promotion programs and that nurses are more supportive by comparison to doctors (Johansson, Stenlund, Lundström, & Weinehall, 2010;Misevicience & Zalnieraitiene, 2013). Correspondingly, Powell and Davies (2012), as outlined above, have found that nurses were more likely to implement pain-manage-ment services.…”
Section: Insider Coalitions With Nursesmentioning
confidence: 99%
“…Now, several authors have argued that the domi-nance of professionals, in particular in medicine, has decreased over the last few decades by emphasizing concepts of deprofessionalization (e.g., Elston, 2004Elston, , 1991Haug, 1988) or prole-tarianization (Mc Kinlay & Arches, 1985). However, these approaches have been criticized for being preoccupied with formal organization and tend to underplay the interactional features and micro-practices in professional organizations (Numerato, Salvatore, & Fattore, 2012) where decoupling still takes place and shields professional work from managerial control. While shifts in the relationship between the state and professionals are evident, medical domi-nance and autonomy has been transformed rather than diminished and the medical profession still is a high-status profession, which has maintained its power, at least on a micro-level in every-day practices in hospitals (Allsop, 2006;Armstrong, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now with the development of an international network of health promoting hospitals in more than 40 countries, health promoting hospitals approach has been used in more than 800 hospitals [12]. However, the development of this network has been slow in developing countries and in spite of recent advances in the field of health care in these countries, the idea of health promotion has progressed slowly in their hospitals [4] and implementation of health promotion services has remained an unknown part in the transformation of the healthcare system in these countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of this approach in Iranian hospital seems to be in the very early stages [8] and there is little evidence of the effectiveness of health promotion standards on health outcomes [12]. However, the results of some studies in Iran and the world suggest that the implementation of health promotion activities in hospitals has led to the improvement of the quality of health services [14,10], improvement of the clinical outcomes after treatment and improve effectiveness of health [15], increase in patient satisfaction, decrease in the length of patient stay in hospital [13,12,3], increase in the welfare of staff and patients [16], raising the awareness and information of patients [8], increase in job satisfaction and motivation of employees [13], improvement of the effectiveness and efficiency in hospitals [9], decrease in treatment complications, repeated admissions and cost of treatment [5] decrease in mortality [3], prevention of diseases, improvement in health indicators [13] and improvement of the quality of life of patients [17]. Then, hospitals must design a specific system for improving and evaluating health promotion and therefore encourage policy-makers and health service administrators to invest resources in HPH [18].…”
Section: Introductionmentioning
confidence: 99%